ANALISIS PENERAPAN STANDAR OPERASIONAL PROSEDUR (SOP) DALAM MENINGKATKAN EFEKTIFITAS KINERJA PEGAWAI PADA KANTOR CAMAT MA’U KABUPATEN NIAS - Golu, Noni Netralis; Baene, Eduard; yamolala, yamolala; Telaumbanua, Aferiaman (Jurnal Tunas Pendidikan, 2024)
Standard Operating Procedures are guidelines or references for carrying out work tasks in accordance with the functions and performance assessment tools of government agencies. The aim of this research is to analyze the application of standard operating procedures (SOP) in improving the effectiveness of employee performance at the Ma'u District Head Office, Nias Regency. This research was carried out as a qualitative type of research with a descriptive approach because this type of research aims to describe and analyze phenomena, events or social activities that are occurring currently at the Mau Subdistrict Office, Nias Regency. The results of this research are: SOP implementation has been implemented but in this case, efficiency has not yet been implemented according to existing Administrative Service SOPs in carrying out duties and responsibilities, so that processing letters by the public takes too long. In this case, the obstacles are due to work delays, discrepancies, non-compliance with existing procedures and limited and delayed information. Efficiency and consistency are very necessary in implementing SOPs in order to maximize existing work. So implementing SOPs is very important because they serve as guidelines or stages in existing work to increase the effectiveness of employee performance.